Characterisation of the immune response to PARV4 - Simmons, RA (2011)
PARV4 is a novel human parvovirus initially identified in an intravenous drug user at risk of HIV infection. PARV4 is a small single stranded DNA virus principally absent from the general population, but common in HCV- and HIV-infected individuals. Until 2009, most published PARV4 studies related to the prevalence of PARV4 in various risk groups. PARV4 has been detected in the liver of HCV-patients and the bone marrow of HIV-patients. Parvovirus B19, the closest related virus, elicits a strong immune response and can cause serious disease. Thus, this project was initiated to characterise the immune response to PARV4, and investigate the clinical significance of this virus. Cohorts of HCV-infected, HIV-infected, HCV-HIV co-infected, healthy and acute parvovirus B19-infected individuals were screened for humoral and cellular responses in both acute and chronic PARV4 infection. HCV- and HIV-related disease progression was also assessed relative to PARV4 infection. This study demonstrates that the highest prevalence of PARV4 infection is found in HCV-HIV co-infected intravenous drug users, and provides additional evidence for parenteral transmission. I present here the first data on the cellular immune response to PARV4 in acute and chronic infection and define PARV4 as a persistent virus. Although no clear correlation could be found between PARV4 and HCV or HIV disease progression, the high prevalence rates emphasize the importance of investigations into emerging infections such as PARV4.